Migración, Medioambiente, y Formación Estatal en la Bolivia Post-Revolucionaria - Soliz, Carmen (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2023)
Book Review Landscape of Migration: Mobility and Environmental Change on Bolivia’s Tropical Frontier, 1952 to the Present. By Ben Nobbs-Thiessen. Chapel Hill: University of North Carolina Press, 2020, p. 342